373 Outcomes of obese patients undergoing gynecologic surgery on an enhanced recovery after surgery (ERAS) program. (18th September 2019) - Harrison, R; Iniesta, MD; Cain, K; Siverand, A; Pitcher, B; Lasala, J; Ramirez, PT; Meyer, LA
Abstract : Objectives: To compare perioperative outcomes of obese vs. non-obese patients undergoing gynecologic surgery on an ERAS program. Methods: We retrospectively reviewed patients undergoing open surgery 11/2014–11/2018. Patients were classified into three categories based on body mass index (BMI) and obesity class:: normal/overweight [BMI 18.0–29.9 kg/m 2 ], class I [BMI 30.0–34.9 kg/m 2 ], class II [BMI 35.0–39.9 kg/m 2 ], and class III or greater [BMI ≥40.0 kg/m 2 ]. Obese patients were matched to non-obese patients by age, procedure date, and surgical indication. Standard statistical methods were utilized. Primary outcome was postoperative length of stay [LOS]. Results: After matching, 696 patients were included in the analysis [normal/overweight, n=348; class I, n=163 class II, n=88; class III or greater, n=97]. All groups had a median postoperative LOS of 3 days. Obese patients had longer procedure times [median OR time: 218 min vs. 192.5 min, p<0.001] and greater estimated blood loss [median EBL: 300 mL vs. 200 mL, p<0.001]. Compliance with individual program elements was not different overall [70.1% vs. 69.8%, p=0.3262], although lower early mobilization was observed among obese patients [89.9% vs. 94.5%, p=0.023]. No differences were observed in severe [grade III-IV] perioperative complications [10.9% vs. 6.6%, p=0.06], reoperation [2.3% vs. 1.4%, p=0.577], and readmission [11.8% vs. 8.0%, p=0.128]. Mild complications [grade I-II] were more frequent in obese patients [62.4% vs. 48.3%, p<0.001], influenced by more wound complications in this group [4.9% vs. 17.8%, p<0.001]. Conclusions: Even after longer operative time and greater blood loss, obese ERAS patients had comparable compliance, perioperative complications, and length of stay to non-obese patients.